Ethnomedical Knowledge of Plants Used for the Treatment of Breast cancer by Jakun community in Kampung Peta Endau Rompin Johor, Malaysia - Mainasara, Muhammad Murtala; Abu Bakar, Mohd Fadzelly; Mohamed, Maryati; Cuevas Linatoc, Alona; Babaji Sanusi, Shuaibu (Journal of Science and Technology, 2017)
Breast cancer is the leading death threat for female apart from heart diseases. In Malaysia, the number of individuals experiencing breast cancer is expected to rise. An ethnobotanical study of plants used by the herbalists, local healers, and inhabitants for the treatment of breast cancer was carried out among the indigenous people of Jakun community in Kampung Peta, Johor, Malaysia. Six key informants were selected based on recognition by the Johor National Park staff and information on therapeutic plants were gathered by semi structured questionnaire. There were only five species of plants belonging to 5 genera and 5 families that have been recorded. Â Most of the plants are set up as juice from fresh plant. 98% of the cures are set up from single plant and taken orally. The utilization of extracts from plant leaves and fruits were usually for the treatment. In all cases, the treatment involved drinking the concentrates for a certain period of time. This study is important to preserve the knowledge of medicinal plants for breast cancer treatment used by Jakun people. The outcome obtained in the study are worth being further investigated for conservation and are also worthy of verifying their ethnomedical claims scientifically.Â